The Effect of Compensation and Work Motivation on The Performance of Food & Bevarage Division Employees at TL Hotel Bandung City - Dewi Oktari, Sari; Rinta Suhardi, Agatha; Budiawan, Andi; Rokayah, Ati; Ananta Patria, Farid (Journal of Management, 2025)
Performance that does not reach the target is suspected to occur due to not maximizing compensation and low work motivation felt by employees. This study aims to test and analyze the effect of compensation and employee motivation on employee performance at TL Hotel Bandung City. The research method uses descriptive and verification, data collection techniques using primary data obtained through questionnaires. The research sample was 33 respondents, the sampling method used purposive sampling. Data analysis techniques using multiple linear regression. From the research results obtained that compensation has a partial effect on performance, while motivation has no significant effect on performance. Competence and motivation affect employee performance simultaneously, with an influence contribution of 28.8% and the remaining 71.2% is influenced by other factors not examined in this study.